2022
DOI: 10.3390/electronics11081231
|View full text |Cite
|
Sign up to set email alerts
|

A Carbon-Nanotube Cold-Cathode Reflex Klystron Oscillator: Fabrication @ X-Band and Returning Electron Beam Realization

Abstract: This paper presents the design and fabrication of a reflex klystron oscillator based on a carbon nanotube (CNT) cold-cathode. An X-band klystron oscillator structure is assembled with a CNT cold-cathode electron gun with an electrostatic focusing, a re-entrant cavity as anode, and a repeller. The electron gun adopts a convex CNT film emitter as the cathode. A re-entrant cavity resonating at 8.376 GHz is fabricated. The study mainly focuses on the returning electron beam in the klystron oscillator structure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, the E-beam transmittance and long-term stability tests (310 h) of the cathode engineering prototype upon the external stimuli were also conducted to verify the stability and reliability of the charging of SiN x -gate, and test results indicate that the cathode can maintain current stability and high E-beam transmittance even under/after external stimulation (Supplementary Figs. [19][20][21][22][23][24][25][26][27][28][29][30][31]18). Therefore, the asprepared cathode with long-term stability and high transmittance under wide-range current and external stimuli is well-suited for the in-space applications mentioned above.…”
Section: The Operation Performances Of the Cathode With Sin X -Gatementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the E-beam transmittance and long-term stability tests (310 h) of the cathode engineering prototype upon the external stimuli were also conducted to verify the stability and reliability of the charging of SiN x -gate, and test results indicate that the cathode can maintain current stability and high E-beam transmittance even under/after external stimulation (Supplementary Figs. [19][20][21][22][23][24][25][26][27][28][29][30][31]18). Therefore, the asprepared cathode with long-term stability and high transmittance under wide-range current and external stimuli is well-suited for the in-space applications mentioned above.…”
Section: The Operation Performances Of the Cathode With Sin X -Gatementioning
confidence: 99%
“…The most straightforward approach is to reduce the gate aperture ratio, whereas the thickness and width of the gate cannot be too small in order to meet the structural robustness and material processing requirements 26 . Alternative approaches, by placing external forces such as electrostatic and magnetic forces on the E-beam, are considered to achieve the E-beam focusing for higher transmittance 27,28 . Han et al developed a curve-shaped elliptical focusing lens above the gate, which achieved a high E-beam transmittance of 95.2%, showing a path for the high-performance X-ray tube 29 .…”
mentioning
confidence: 99%
“…[47][48][49] Alternative approaches, by placing external forces such as electrostatic and magnetic forces on the E-beam, are considered to achieve the E-beam focusing for higher transmittance. [50][51][52][53] J. S. Han et al developed a curve-shape elliptical focusing lens above the gate, which achieved a high E-beam transmittance of 95.2%, showing new path for the highperformance X-ray tube. 54 J. Zhang et al demonstrated the effectiveness of introducing external magnetic field to enhance the performance of the gate-type cathodes.…”
mentioning
confidence: 99%